Exploring Difficulties of Master’s Degree Students in Learning Linear Algebra - Subedi, Abatar (Perspectives on Higher Education, 2025)
This paper aims to explain the difficulties of students in learning algebraic concepts in linear algebra course at master degree level. For, I conducted a case study of ten master’s degree students selected purposively, who are studying linear algebra course in the department of mathematics education, Tribhuvan University, Kirtipur in 2024. I used semi-structured interview guidelines, observation notes and performance test to explore students’ difficulties in learning linear algebra. The results shows that students have conceptual as well as procedural difficulties in learning algebraic concepts, proving theorems, solving numerical problems, and constructing examples of abstractions. Likewise, they have poor prerequisites to learn linear algebra which make them difficult to learn new concepts at master level. Thus, it is suggested that the teacher who are teaching linear algebra course at that level need to have develop strong prerequisites to improve their students’ performance and to mitigate conceptual as well as procedural difficulties to learn linear algebra.